Tailoring implementation of a youth-focused mental health intervention in Sierra Leone using an implementation blueprint methodology - Alethea Desrosiers; Bidemi Carrol; Jacqueline Hayes; Fatoma Momoh; Haley Ritsema; Hannah E. Frank; Unisa Jalloh (BMC Public Health)
Abstract Background Identifying contextual factors that might support or hinder implementation of evidence-based mental health interventions for youth in low- and middle- income countries may improve implementation success by increasing the alignment of intervention implementation with local needs and resources. This study engaged community partners in Sierra Leone to: (a) investigate barriers and facilitators to implementing a mental health intervention within Sierra Leone’s schools; (b) develop an implementation blueprint to address identified implementation barriers; (c) explore the feasibility of using the implementation blueprint methodology in Sierra Leone. Methods We recruited Ministry of Education Officials (n = 2), teachers (n = 15) and principals (n = 15) in Sierra Leone to participate in needs assessment qualitative interviews. We used a rapid qualitative analysis approach to analyze data. Three team members summarized transcripts based on domains aligned with the structured research questions, organized themes into a matrix, and identified and discussed key themes to arrive at consensus. We then reconvened community partners to discuss implementation strategies that could address identified barriers. Participants ranked barriers according to high/low feasibility and high/low importance and selected implementation strategies for the blueprint. Results Qualitative results revealed several implementation barriers: teacher/parent/student buy-in; teacher motivation; scheduling time; limited funding; waning interest; daily hardships outside of school. Strategies selected included: develop/distribute educational materials; conduct education meetings/outreach; identify and prepare champions; access new funding. Conclusions Engaging community partners to develop an implementation blueprint for integration of a mental health intervention within Sierra Leone’s schools was feasible and may increase implementation effectiveness.